Children's Voice and Voice Disorders - McAllister, Anita; Sjölander, Peta (Seminars in Speech and Language, 2013)
This article discusses the differences between children's voices and adult voices. We give an overview of the anatomy in the head and neck and specifically the anatomy of the respiratory system and the larynx. We also describe the development of children's voices including different physiological measures and voice quality. The development and consequences for voice production and voice quality are addressed and related to gender differences in the growing child. We also discuss the prevalence of voice problems and hoarseness in children. Environmental and other factors contributing to voice problems in children are described, and finally, issues related to intervention and evidence-based practice are discussed.
Keywords: Children; voice; development; dysphonia; environment; voice therapy; evidence-based